2012
DOI: 10.5402/2012/595734
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and Hepatic Haemodynamic Alterations among Egyptian Children with Liver Cirrhosis

Abstract: Background. Alterations in thyroid hormones regulation and metabolism are frequently observed in patients with cirrhosis. Aims. To assess alterations in thyroid volume (TV), haemodynamics, and hormones in patients with cirrhosis and their relation to hepatic arterial haemodynamics, and disease severity. Methods. Forty cirrhotic patients were compared to 30 healthy subjects regarding TV, free triiodiothyronine (fT3), free tetraiodothyronine (fT4), thyroid stimulating hormone (TSH), and pulsatility and resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
3
8
0
2
Order By: Relevance
“…Decreased levels of TT3 and TT4 have been observed in cirrhotic patients, with a negative correlation with cirrhosis severity . The FT3 level was also found to be lower in cirrhotic patients than in controls . However, previous studies have revealed contradictory FT4 alterations in cirrhotic patients .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Decreased levels of TT3 and TT4 have been observed in cirrhotic patients, with a negative correlation with cirrhosis severity . The FT3 level was also found to be lower in cirrhotic patients than in controls . However, previous studies have revealed contradictory FT4 alterations in cirrhotic patients .…”
Section: Discussionmentioning
confidence: 88%
“…18,38,39 The FT3 level was also found to be lower in cirrhotic patients than in controls. 40 However, previous studies have revealed contradictory FT4 alterations in cirrhotic patients. 41 is available on fibrosis or early cirrhosis, especially the dynamic alterations in thyroid hormones with the METAVIR fibrosis score.…”
Section: Discussionmentioning
confidence: 99%
“…Birçok çalışmada siroz hastalarında HARI değerinin arttığı gösterilmiştir (2,5,10,(13)(14)(15). El-Kabbany ve ark.…”
Section: Discussionunclassified
“…Doppler US, B mod US bulguları normal olan kronik karaciğer hastalarında dahi karaciğer hemodinamisindeki değişiklikleri belirler ve ayrıca kalitatif ve kantitatif ölçümlere olanak sağlar (7). Birçok araştırmacı farklı Doppler parametreleri kullanarak bu hemodinamik değişiklikleri değerlendirmeye çalışmıştır (2,5,(8)(9)(10). Kronik karaciğer hastalığı ve sirozu ayırmada fibrozis indeksi tanımlanmış ve fibrozis indeksinin siroz hastalarında daha yüksek olduğu bulunmuştur (11).…”
Section: Introductionunclassified
“…Non-alcoholic fatty liver diseases and abnormal liver enzymes are significantly associated with hypothyroidism and the the prevalence of liver diseases and enzymes increase steadily with increasing grades of hypothyroidism [34]. Furthermore, a decrease in serum T3 concentration and T3:T4 ratio is frequently observed in patients with liver cirrhosis probably due to impaired conversion of T4 to T3 in the liver [35]. Thyrotoxicosis is also associated with a variety of abnormalities of liver function [36] and results from a recent study suggests that low FT4 concentrations are associated with hepatic steatosis [37].…”
Section: Discussionmentioning
confidence: 99%